Analysis of Leadership Models in Islamic Education Management: A Case Study on Integrated Islamic Elementary Schools in Serang City - Sudaryono (Penerbit Minhaj Pustaka, 2025)
The success or failure of a school depends on the quality of educators and education personnel and the leadership model of the principal in the management of Islamic education in the school. The factors behind this include poor leadership roles in developing the quality of educators and education personnel, such as the lack of competence of educators. In addition, factors that are quite influential are the management factor and the leadership role of the principal in improving the quality of educators and education personnel. The formulation of the problem is how the leadership and management model of the principal in implementing the vision and mission in improving the quality of educators and education at SDIT Al-Izzah Serang City. What are the obstacles to implementing the leadership and management model of school principals in implementing the vision and mission in improving the quality of educators and education at SDIT Al-Izzah. To find out the obstacles in management and leadership, the principal implements the vision and mission in improving the quality of educators and education at SDIT Al-Izzah. This study is a qualitative research with a literature review analysis method. The data collection method uses interview, observation and documentation techniques. The results of the study show that: the leadership and management model of the principal implementing the vision and mission in improving the quality of educators and education at SDIT Al-Izzah is optimal. Improving teachers' pedagogic competence is carried out with activities such as coaching and evaluation, holding workshops, IT-based learning training, standardizing the assessment system with the procurement of value processing applications. Teachers' personality competencies are fostered to improve their personality abilities that are steady, noble, wise, and authoritative and become role models for students. Teachers' social competence is honed through the 5 S program (smile, greeting, greeting, politeness, and courtesy), continuous training as tausiyah officers, tarbiyah, student guardian meetings, meetings with student guardian associations, meetings with committees. Teachers' professionalism is fostered by their ability to master subject matter broadly and deeply, which is carried out continuous improvement.